Fatigue and Fracture of Traditional and Advanced Structural Alloys - Berto, Filippo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The fatigue behavior of traditional and advanced materials is a very relevant topic in different strategic applications impacting and affecting our daily lives. The present Special Issue invites papers to update readers on the state of the art on this important topic. Both review and original manuscripts are welcome. Special attention will be dedicated to innovative materials and innovative manufacturing processes or post-treatments able to improve the fatigue life and reliability of a structural component. Scale effect will be also fully treated focusing on different applications and multiscale approaches aimed at understanding structural integrity under cyclic loadings. This state of the art perspective will help engineers, designers and people from the academy gain an updated view on this very challenging topic which is nowadays very important due to the advances in manufacturing technologies that allow complex new materials to be fabricated.